Effect of temperature on thermophilic composting of aquaculture sludge: NH3 recovery, nitrogen mass balance, and microbial community dynamics - Koyama, Mitsuhiko; Nagao, Norio; Syukri, Fadhil; Abd Rahim, Abdullah; Kamarudin, Mohd Salleh; Toda, Tatsuki; Mitsuhashi, Takuya; Nakasaki, Kiyohiko (Elsevier, 2018)
Development of thermophilic composting for maximizing NH3 gas recovery would enable the production of a nitrogen source which is free from pathogen/heavy metal, for the cultivation of high-value microalgae. The present study examined the effect of NH3 recovery, nitrogen mass balance, and microbial community dynamics on thermophilic composting of shrimp aquaculture sludge. The emission of NH3 gas at 60 and 70 °C was 14.7% and 15.6%, respectively, which was higher than that at 50 °C (9.0%). The nitrogen mass balance analysis revealed that higher temperatures enhanced the solubilization of non-dissolved nitrogen and liberation of NH3 gas from the produced NH4+-N. High-throughput microbial community analysis revealed the shift of the dominant bacterial group from Bacillus to Geobacillus with the rise of composting temperature. In conclusion, thermophilic composting of shrimp aquaculture sludge at 60–70 °C was the most favorable condition for enhancing NH3 gas recovery.